Cognitive functioning in children and adolescents with cerebral palsy: protocol for the Danish CPCog-Youth study - Camilla Funch Uhre; Ida Dyhr Caspersen; Carsten Lose; Gija Rackauskaite; Ro Robotham; Christina E. Hoei-Hansen (BMC Pediatrics, 2024)
Abstract Background Many children and adolescents with cerebral palsy (CP) experience cognitive difficulties, impacting their academic, social, and emotional well-being. A Danish study from 2023 revealed that merely 40% of individuals with CP complete their elementary school education, and previous neuropsychological studies have found that most children and adolescents with CP experience cognitive difficulties. Yet, cognitive functioning is often assumed rather than assessed, and CP follow-up programs focus predominantly on physical functioning. Recognizing this gap, we aim to investigate cognitive functioning in children and adolescents with CP in mainstream schools in Denmark, using standardized neuropsychological tests. Our objective is to provide valuable insights to guide clinical practice on cognitive assessment and intervention, ultimately fostering a more effective support system for individuals with CP. Methods The study employs a cross-sectional design, involving 100 children and adolescents with CP aged 11–15 years attending mainstream schools in Denmark. Cognitive assessment includes the core battery from a proposed Nordic test protocol for children and adolescents with CP – the CPCog – encompassing general cognitive functioning (intelligence), executive functions, and visuo-motor skills. Supplementary tests cover verbal and nonverbal short-term memory, attention, fatigue, and mental health. The assessment protocol will also be evaluated by parents of participating children and adolescents with CP. The project is conducted collaboratively by the neuropsychological teams at three assessment sites, in conjunction with the Center for Cerebral Palsy, Rigshospitalet, Aarhus University Hospital, and Aalborg University Hospital. The study benefits from an external advisory board comprising leading international CP experts. Discussion Cognitive difficulties in children and adolescents with CP are often overlooked. Few cognitive studies exist, with some providing only estimated cognitive functioning. The CPCog-Youth study will help advance our understanding of the cognitive challenges experienced by children and adolescents attending mainstream schools. The findings will contribute to the development of targeted cognitive assessment and intervention programs for individuals with CP, addressing this commonly neglected aspect of care. By also seeking feedback from participating families and the involved neuropsychologists, we aim to investigate whether the proposed cognitive assessment is feasible and beneficial in real-world settings. Trial registration The study was registered on ClinicalTrials.gov on June 27, 2023 (ID: NCT05921422).